Effectiveness of inquiry-based learning versus traditional lecture methods in teaching biology concepts: A comparative study - Apor, Mary Ann A. (Edelweiss Applied Science and Technology, 2025)
This study investigates the effectiveness of inquiry-based learning (IBL) compared to traditional lecture methods in teaching biology concepts to undergraduate students. A quasi-experimental design was employed with 120 students across four sections of an introductory biology course over one semester. Two sections (n=60) received instruction through inquiry-based learning approaches, while two control sections (n=60) used traditional lecture methods. Pre- and post-assessments measured conceptual understanding, with additional measures for student engagement and retention. Results indicated that students in the inquiry-based learning group demonstrated significantly higher post-test scores (M=78.5, SD=8.2) compared to the traditional lecture group (M=71.3, SD=9.1), t(118)=4.67, p<0.001. Effect size calculations revealed a medium to large effect (Cohen’s d=0.85). Students in the IBL group also showed greater improvement in critical thinking skills and reported higher levels of engagement. These findings suggest that inquiry-based learning approaches are more effective than traditional lecture methods for teaching biology concepts, particularly in promoting deeper conceptual understanding and student engagement.